Cannibalistic behaviour of Sutchi catfish (Pangasianodon hypophthalmus) larvae under different light conditions - Ismail, Khairul Muttaqin; Mohammad Noor, Normawaty; Mukai, Yukinori (2017)
Sutchi catfish Pangasianodon hypophthalmus larvae have high mortality rate in hatchery because of strong cannibalism. Many factors were influencing the cannibalism rate. One of them is light condition. In previous study, the sutchi catfish larvae show higher mortality in bright light condition than in dim light condition under white fluorescent lamp (Mukai, 2011). So far, there were no study conducted about the effect of different light wavelengths on the sutchi catfish larvae. In this study, the cannibalistic behaviours of sutchi catfish larvae was investigated under different light wavelengths (white, blue, green, yellow and red) and light intensities (0.0014, 0.014, 0.14 and 1.4 μmol m-2 s-1). Ten larvae (4-14 days old) were placed in a glass basin under different light conditions in a dark room. The behaviours of the larvae were recorded for 30 minutes after adaptation. The cannibalistic behaviours (biting, resting and swimming activity) of the larvae were analysed from the video recorded.